Variability of Textural Characteristics of Sandur Deposits of Fláajökull and Falljökull (SE Iceland) - Angiel Piotr (Miscellanea Geographica, 2006)
Studies conducted on the sandurs of Fláajökull and Falljökull aimed at the reconstruction of the dynamics of braided rivers based on the grain size parameters of deposits. The goal of the project was to estimate the degree of deposit transformation and of changes of grain size characteristics as related to the length of transport in contemporary sandur rivers.